Stress Adaptation, Prophylaxis and Treatment 1999
DOI: 10.1007/978-1-4615-5097-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic stress-induced oxidative gastrointestinal mucosal injury in rats and protection by bismuth subsalicylate

Abstract: Reactive oxygen species (ROS) are implicated in the pathogenesis of stress-induced gastrointestinal mucosal injury. In the present study, we have investigated the effects of acute and chronic stress on the enhanced production of ROS including superoxide anion [SA; as determined by cytochromec reduction (CCR)] and hydroxyl radicals (OH), and correlated the enhanced production of these free radicals with increased lipid peroxidation, membrane microviscosity and DNA fragmentation, indices of oxidative tissue dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 20 publications
0
31
1
1
Order By: Relevance
“…JANG et al [21] showed that a supplementation of a blend of commercial essential oils [14,15] . Previous studies reported that dietary antioxidants, such as vitamin C, E, flavonoids, and phenolic can reduce oxidative damage in animals which is generated by different stress sources [22,23] . Jamroz and Kamel [24] who observed improvements of 7.7% in feed conversation ratio fed a diet supplemented with a plant extract containing capsaicin, cinnamaldehyde and carvacrol in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…JANG et al [21] showed that a supplementation of a blend of commercial essential oils [14,15] . Previous studies reported that dietary antioxidants, such as vitamin C, E, flavonoids, and phenolic can reduce oxidative damage in animals which is generated by different stress sources [22,23] . Jamroz and Kamel [24] who observed improvements of 7.7% in feed conversation ratio fed a diet supplemented with a plant extract containing capsaicin, cinnamaldehyde and carvacrol in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated an increase (Bagchi et al, 1999;Sivonova et al, 2004), decrease (Atanackovic et al, 2002;Yamaguchia et al, 2002) and no change (Huang et al, 2010) in indices of oxidative stress (i.e. plasma markers and ROS levels) in response to acute mental stress and during periods of lifestyle stress.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, stressful situations (i.e. exam periods (Sivonova et al, 2004) and public speaking (Yamaguchia et al, 2002)) and study model (human (Atanackovic et al, 2002) and animal (Bagchi et al, 1999) models) have varied significantly between studies, making it hard to draw valid and robust conclusions. To our knowledge, this was the first study utilising well standardized laboratory models of both acute inflammation and mental stress to test the sole influence of baseline inflammation on the oxidative stress responses to mental stress in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bagchi et al (1999) reported that acute and chronic stress exposure increases mucosal lipid peroxidation, cytochrome c reduction, and hydroxyl radical production in rat intestinal mucosa. Such results indicate that oxygen free radicals, including superoxide anions and hydroxyl radicals, are involved in the pathogenesis of acute and chronic stress-induced gastrointestinal injury, and can result in lipid peroxidation.…”
Section: Effects Of Heat Stress On Cell Dynamics Of Broiler Chicken Smentioning
confidence: 99%